2010
DOI: 10.3109/00952990903544851
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Injection Drug Use Is Associated with Lower Percent Body Fat in a Multi-Ethnic Cohort of HIV-Positive and HIV-Negative Drug Users from Three U.S. Cities

Abstract: Background-The clinical implications of lower body weight in drug using populations are uncertain given that lower mean weights may still fall within the healthy range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 24 publications
3
31
1
1
Order By: Relevance
“…Importantly, the amphetamine and heroin using groups were all using these respective drugs weekly, while in the morphine group the weekly use of morphine was just under 50%, and all three groups had similar probabilities of using alcohol and cannabis daily. Some previous studies have found life style factors associated with injecting drug use influenced BMI, rather than the specific type of drug used (Tang et al, 2010;Mallett, Rosenthal, & Keys, 2005). However, we found strong associations between different groups of drug users with BMI.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Importantly, the amphetamine and heroin using groups were all using these respective drugs weekly, while in the morphine group the weekly use of morphine was just under 50%, and all three groups had similar probabilities of using alcohol and cannabis daily. Some previous studies have found life style factors associated with injecting drug use influenced BMI, rather than the specific type of drug used (Tang et al, 2010;Mallett, Rosenthal, & Keys, 2005). However, we found strong associations between different groups of drug users with BMI.…”
Section: Discussioncontrasting
confidence: 82%
“…When comparing the BMI ranges of our sample of injecting drug users with the general population, our study shows that people who regularly inject drugs have a tendency towards a lower BMI than the general population (McCombie et al, 1995;Tang et al, 2010), with poor nutrition and metabolic complications believed to be implicating factors (Islam et al, 2002;Tang et al, 2010). In keeping with the literature (Cofrancesco et al, 2007;Galea & Vlahov, 2002: Adrian & Barry, 2003, characteristics of the sample population that were significantly associated with BMI were being female, homelessness, and high levels of psychological distress, though as stated above these factors were not significant after accounting for different drug using groups.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Since heroin addicted individuals are usually malnourished (25,26), the impaired status of certain nutrients should also be taken into account when evaluating oxidative stress in this population.…”
Section: Discussionmentioning
confidence: 99%
“…También se podría pensar que los consumidores de marihuana presenten un menor índice de masa corporal debido al policonsumo de sustancias psicoactivas 54,55 , dada la exposición que tienen a otras sustancias psicoactivas como la heroína, cocaína, bazuco y demás, de las cuales se conocen sus efectos devastadores sobre el estado nutricional de sus consumidores [56][57][58] . De la misma manera, se debe continuar la investigación sobre la respuesta fisiológica frente a los cannabinoides en diferentes etapas de la adicción, el cuerpo desarrolla una tolerancia frente a los efectos producidos por el THC, debe estudiarse el papel de antagonistas del CB1 como el cannabidiol en esta etapa, ya que el estudio de Ignatowska y Cols.…”
Section: Efectos Del Sistema Cannabinoide Sobre El Estado Nutricionalunclassified